2017
DOI: 10.1128/jcm.01615-16
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution, Population Structure, and Antimicrobial Resistance of Group B Streptococcus Strains Recovered from Colonized Pregnant Women

Abstract: Using serotyping, multilocus sequence typing, and whole-genome sequencing (WGS) of selected strains, we studied the population structure of 102 group B Streptococcus (GBS) isolates prospectively sampled in 2014 from vaginal/ rectal swabs of healthy pregnant women in metropolitan Toronto, Canada. We also determined the susceptibilities of each of the colonizing isolates to penicillin, erythromycin, clindamycin, tetracycline, and other antimicrobial agents. Overall, we observed a high rate of tetracycline resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
7
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 61 publications
11
101
7
7
Order By: Relevance
“…(11,28) Data from North America reported rates of resistance to erythromycin and clindamycin ranging from 27.4% to 36% and 27.4% to 33%, respectively. (11,29) High rates of GBS resistance for both antimicrobials were reported in Italy (32.2% for erythromycin and 43.8% for clindamycin) (30) and China (78.6% for erythromycin and 64.3% for clindamycin) (WANG et al, 2015). (10) In contrast, lower rates of resistance were detected in Swiss (14.6% for erythromycin and 8.2% for clindamycin) (12) and Saudi Arabia (15.7% for erythromycin and 5.1% for clindamycin).…”
Section: Resultsmentioning
confidence: 89%
“…(11,28) Data from North America reported rates of resistance to erythromycin and clindamycin ranging from 27.4% to 36% and 27.4% to 33%, respectively. (11,29) High rates of GBS resistance for both antimicrobials were reported in Italy (32.2% for erythromycin and 43.8% for clindamycin) (30) and China (78.6% for erythromycin and 64.3% for clindamycin) (WANG et al, 2015). (10) In contrast, lower rates of resistance were detected in Swiss (14.6% for erythromycin and 8.2% for clindamycin) (12) and Saudi Arabia (15.7% for erythromycin and 5.1% for clindamycin).…”
Section: Resultsmentioning
confidence: 89%
“…In the remaining instances, GBS was first isolated from both mother and infant at the 18 third timepoint (dyad 6, week 2) or from the mother prior to isolation from the infant (dyad 19 20). 20 21 22 Figure 2A&B: Phylogenetic relationship between GBS isolates from mother-infant dyad 23 17 and three other genomes (2 mothers and two infants) 24 The genomes are labelled with the dyad number from which they were derived. Mother17 & 25…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have associated ST196 with serotype IV [22]. We are aware of only one other study which reported one strain out of 102 prospectively collected strains to be ST196 with a serotype II capsular backbone [23].…”
Section: Discussionmentioning
confidence: 98%
“…6,9 Since the implementation of these recommendations, the rate of invasive pneumococcal disease in Canada has been stable, at about 9.6 cases per 100 000. 10 There has been a decrease in the incidence of pneumococcal serotypes covered by Pneu-C-13, but also a possible increase in serotypes not covered by the pneumococcal vaccines, specifically in the asplenic population. 10,11 The current Canadian vaccine guidelines can be found online at www.…”
Section: Vaccinationsmentioning
confidence: 99%
“…10 There has been a decrease in the incidence of pneumococcal serotypes covered by Pneu-C-13, but also a possible increase in serotypes not covered by the pneumococcal vaccines, specifically in the asplenic population. 10,11 The current Canadian vaccine guidelines can be found online at www. phac-aspc.gc.ca/publicat/cig-gci/index-eng.php.…”
Section: Vaccinationsmentioning
confidence: 99%